SDGs CONCEPT ON MADRASSA IBTIDAIYAH POLICIES AS A WAY TO ENHANCE ECO-FRIENDLY EDUCATION - Sholihah, Mar’atus; Khoirul Umamah, Fitriah; Izza Putri, Frida Nur; Alfiah, Alfiah; Qomariah, Khusnul (International Conference on Humanity Education and Society (ICHES), 2025)
Eco-friendly awareness of the environment was declared ten years ago globally, but has challenges in its implementation across all sectors, including education. This condition is caused by society’s habits that have not been developed generally, aswell as students in madrassa ibtidaiyah, even though the central and local governments have written several policies. This research aims to describe a study about the concept of Sustainable Development Goals on madrassa ibtidaiyahpolicies as a way to enhance eco-friendly education for the environment. The research method uses a mixed method with a complex mixed methods design through a triangulation strategy analysis. The research results show that the SDGsconcept implementation on madrassa ibtidaiyah policies is enhanced from three goals: quality education, gender equality, and reduced inequality. These three goals stated in Pancasila Student Profile policies (P5) on the Dimension of Commitmentto Religious Faith, Reference toward God Almighty, and Strong Moral Character; Rahmatan lil ‘Alamin Student Profile on the Dimension of Sustainable Living, Local Wisdom, Unity in Diversity, Pancasila Democracy, Equity, and Tolerance; also GreenSchool with indicators on Environmentally Sustainable Policy, EnvironmentallyBased Curriculum Implementation, Participatory Environment-Based Activities, and Environmentally Friendly Support Facilities Management.